The Role of Neck Input in Producing Corrective Saccades in the Head Impulse Test - Iwasaki, Shinichi; Kamogashira, Teru; Fujimoto, Chisato; Kabaya, Kayoko; Kinoshita, Makoto; Yamasoba, Tatsuya (Frontiers in Neurology, 2022)
Background The head impulse test is a valuable clinical test that can help identify peripheral vestibular dysfunction by observing corrective saccades that return the eyes to the target of interest. Corrective saccades have been classified as covert if the onset occurs before the end of the head impulse and as overt if they occur afterwards. However, the mechanism that trigger these saccades remain unclear. Objective The objective of this study was to examine the role of neck input in generating overt as well as covert saccades. Methods Sixteen patients (9 males and 7 females: age 35-80 years, average 62.7 years old) who showed corrective saccades during the head impulse test were included. Twelve patients had unilateral vestibular dysfunction, and 4 patients had bilateral vestibular dysfunction. Patients underwent both the head impulse test (HIT) and the body impulse test (BIT) in a randomized order. While the head is rotated horizontally in HIT, the body is rotated horizontally in BIT. During BIT, the neck is fixed by a cervical collar (neck lock extrication collar) to reduce somatosensory input from the neck. The head movements and eye movements were recorded and analyzed by the video HIT recording system. Results In all 16 patients, corrective saccades were observed in HIT as well as in BIT. While there were no significant differences in peak head velocities between HIT and BIT (p = 0.33, paired t-test), the VOR gain in BIT was significantly smaller than that in HIT (p = 0.011, paired t-test). The number of overt saccades per trial in BIT was significantly decreased compared to that in HIT (p < 0.001, paired t-test) whereas there were no significant differences in the number of covert saccades between the two tests. The proportion of overt saccades among all corrective saccades in BIT was significantly lower than the proportion in HIT (p < 0.001, paired t-test). Conclusions Somatosensory input from the neck contributes to the generation of overt saccades and reinforces the vestibulo-ocular reflex complementing the retinal slip during high frequency head movements.